The Use of Religious-Based Prompt Methods in Preventing Violence Against Children in Group B at Tunas Mekar Kindergarten - Widya Maharani; Nurhayati Nurhayati; Amrullah Amrullah; Andi Agusniatih (Journal of Educational Sciences, 2026)
This study aims to examine the application of religious-value-based prompt methods in preventing violence against young children and to analyze their impact on children’s social skills. The study employed a descriptive qualitative approach with a correlational design, conducted at Tunas Mekar Kindergarten in Palu during the 2025/2026 academic year, with 18 children from Group B as the subjects. Data collection techniques included observation, interviews, and documentation, while data analysis utilized percentage calculations and qualitative interpretation. The results of the study indicate that the application of prompts based on religious values is effective in improving children’s emotional regulation skills, non-violent social behavior, as well as their understanding and application of religious values. In the first week, the majority of children were in the “beginning to develop” category (55.56%) and the “not yet developed” category (24.07%). Following the implementation of the prompts method in the second and third weeks, there was an increase in the “developing as expected” (37.03%) and “developing very well” (29.62%) categories, and no children remained in the “not yet developing” category. Interview results with teachers also indicated that learning became more active, interactive, and enjoyable, and that children were better able to exhibit non-violent social behavior. Thus, prompts based on religious values are effective in improving the social skills of young children and can serve as a learning strategy to prevent violence against children in school settings.